Akulturasi Pernikahan Etnik Mandailing di Desa Simonis Labuhanbatu Utara - Herawati, Desi; Fahira, Jihan; Batubara, Epridasari; Harahap, Aftitah; Siregar, Yusra Dewi (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2023)
This study examines the cultural acculturation in Mandailing ethnic marriages in Desa Simonis, Labuhanbatu Utara Regency, North Sumatra. Focusing on how the marriage process serves as a medium for cultural integration in a multiethnic society, the research identifies various cultural elements interacting and adapting within marriage practices. Using a qualitative approach, the study involves direct observation, interviews with local traditional leaders and community members, and analysis of documents related to marriage traditions. The findings reveal that Mandailing marriages in Desa Simonis not only incorporate local Mandailing customs but also blend elements of Malay and Hindu cultures, creating a rich and dynamic celebration. This acculturation is reflected in various ritual aspects, such as the tepung tawar ceremony, upah-upah, and Endeng-Endeng dance, which show the integration of symbols and practices from different cultures. The study highlights the role of marriage as a key mechanism in the preservation and transformation of culture, as well as how marriage functions as a bridge between different traditions and communities. This research provides insights into the ongoing process of cultural acculturation in multiethnic societies and its contribution to the formation of new cultural identities in the region.